Massive Scrotal Edema: An Unusual Manifestation of Obstructive Sleep Apnea and Obesity-Hypoventilation Syndrome - Stephanie E. Dreifuss; Ernest K. Manders (Case Reports in Medicine)
Obstructive sleep apnea (OSA) may occur in association with obesity-hypoventilation (Pickwickian) syndrome, a disorder of ventilatory control affecting individuals with morbid obesity. Through the pressor effects of chronic hypercapnia and hypoxemia, this syndrome may result in pulmonary hypertension, right heart failure, and massive peripheral edema. We present a case of severe scrotal edema in a 36-year-old male with OSA and obesity-hypoventilation syndrome. A tracheostomy was performed to relieve hypoxemia and led to dramatic improvement of scrotal edema. No scrotal surgery was necessary. Followup at two months showed complete resolution of scrotal edema, improvement in mental status, and normalization of arterial blood gas measurements. This case demonstrates that OSA and obesity-hypoventilation syndrome may present with massive scrotal edema. Furthermore, if OSA is recognized as the cause of right heart failure, and if the apnea is corrected, the resultant improvement in cardiac function may allow reversal of massive peripheral, including scrotal, edema.